ADVANCEMENTS IN UNDERSTANDING THE DEVELOPMENT OF CANDIDA-ASSOCIATED DENTURE STOMATITIS - Cosmin Bida; Teona Tudorici; Dan Nicolae Bosinceanu; Octavian Ionut Tunaru; Dana Gabriela Budala (Romanian Dental Association for Education, 2024)
Candida-associated denture stomatitis is a common and persistent issue among complete denture wearers. This paper explores new insights into the development of this condition, focusing on pathogenic factors and mechanisms that facilitate Candida colonization and proliferation. The role of biofilm formation on denture surfaces and the influence of local and systemic risk factors, such as poor oral hygiene, smoking, and systemic diseases, are analyzed. Additionally, recent innovations in diagnostic and treatment methods are discussed, including the use of antimicrobial agents and probiotics, as well as advancements in denture materials. By understanding these aspects more deeply, this paper aims to provide practical solutions for the effective prevention and management of Candida-associated denture stomatitis, ultimately contributing to the improvement of the quality of life for denture wearers. This comprehensive review synthesizes the latest research and clinical practices to guide dental professionals in addressing this prevalent issue.